2007
DOI: 10.1016/s1472-6483(10)60769-9
|View full text |Cite
|
Sign up to set email alerts
|

High rate of biological loss in assisted reproduction: it is in the seed, not in the soil

Abstract: The vast majority of embryos produced in vitro and transferred fail to develop into an infant, supporting the concept that only a small fraction of embryos is destined to become a live birth. One of the main reasons for such a low embryo-to-infant ratio is the remarkably high number of embryos that after preimplantation genetic diagnosis are found to have a chromosome imbalance. This study reports the overall biological wastage from oocytes inseminated to ongoing pregnancies in patients undergoing preimplantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 11 publications
3
25
0
Order By: Relevance
“…In a previous report, we reported that 77.1 % (13/57) of embryos displayed a chromosomal abnormality for the advanced maternal age group (above 35 years old) [17]. The chromosomal abnormality rate for women 43 years or beyond in our own analysis was found to be 80.…”
Section: Discussionsupporting
confidence: 48%
“…In a previous report, we reported that 77.1 % (13/57) of embryos displayed a chromosomal abnormality for the advanced maternal age group (above 35 years old) [17]. The chromosomal abnormality rate for women 43 years or beyond in our own analysis was found to be 80.…”
Section: Discussionsupporting
confidence: 48%
“…Is it possible, that as seen through the course of reproductive life, that some follicles are doomed to atresia, and this cannot be corrected with ideal culture systems under any circumstances? This is highly reminiscent of the clinical situation, where a fraction of oocytes retrieved after gonadotropic stimulation seems always incapable of supporting blastocyst development and the generation of healthy babies (Patrizio et al 2007 ). Accordingly, in vitro culture results in a high level of follicle attrition by atresia.…”
Section: Recreating the Crime Scene: Models Used Dissect The Control mentioning
confidence: 99%
“…Despite significant advancements in the field, the process of human reproduction remains inefficient with many unanswered biological questions [2,3]. Previous work analyzed the number of embryos transferred compared to the number of live births and showed that the majority of embryos produced during IVF cycles (about 85%) and chosen for transfer fail to result in a live born infant [4].…”
Section: Introductionmentioning
confidence: 99%